Peningkatan Pengetahuan Petugas Kesehatan Tentang Ketepatan Kodefikasi Penyakit Berdasarkan Pedoman Icd-10 Di Uptd Puskesmas Barambai - Soraya .; Rabiatul Adawiah; M.Heriyadi .; Rahardina Dwi Cantika (CV. ITTC INDONESIA, 2026)
Accurate disease coding is a critical component of the health information system, as it directly affects data quality, morbidity reporting, healthcare financing claims, and managerial decision-making in healthcare facilities. At the Barambai Subdistrict Primary Health Center, inaccuracies in diagnosis coding based on ICD-10 guidelines are still identified. These issues are mainly caused by limited understanding among healthcare personnel, high workload, and the lack of continuous and structured coding training. Such conditions may negatively impact the quality of health data and the accuracy of healthcare service reporting. This program aims to enhance the knowledge and skills of healthcare personnel in performing accurate and consistent disease coding in accordance with ICD-10 guidelines through theory-based education and case study–based training. The program is expected to strengthen the competencies of staff in the Health Information Management Division in applying diagnosis codes accurately, systematically, and in compliance with established standards, thereby supporting improvements in the quality of medical records and health information systems at the primary healthcare level. In addition, this activity contributes to the achievement of Sustainable Development Goals (SDGs), particularly Goal 3 on ensuring healthy lives and promoting well-being, by strengthening the health system. It also supports the role of higher education institutions in community service activities, especially in improving the quality of human resources in the field of health information management.